Analysis of Understanding of Islamic Work Ethic - Hanif Hanif; Moh. Mukri; Is Susanto (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
Work ethic is a person's attitude and view at work, sourced from self-quality, realized based on values ​​and implemented in activities at work. A work ethic based on Islamic values ​​will form a Muslim full of responsibility and hard work in carrying out his duties at work. At a practical level, an understanding of the Islamic work ethic will have a major impact on work. The results of this study indicate that in general the understanding of the Islamic work ethic of the employees of UIN Raden Intan Lampung and IAIN Metro is in accordance with the theory of Islamic work ethic. However, in practice not all employees carry out an Islamic work ethic which includes work to seek sustenance, work is worship, work professionally, work hard, respect time (discipline), uphold honesty. According to the Islamic perspective, work is part of fulfilling the needs of life which are divided into primary, secondary and tertiary needs. These three needs are very important for the running of human life in general and humans in particular. If it does not work, then humans will naturally experience difficulties which will eventually fall into sin.